2016
DOI: 10.1155/2016/3065657
|View full text |Cite
|
Sign up to set email alerts
|

Angiofibroma Originating outside the Nasopharynx: A Management Dilemma

Abstract: Background. Angiofibroma is a benign tumor, consisting of fibrous tissue with varying degrees of vascularity, characterized by proliferation of stellate and spindle cells around the blood vessels. It most commonly arises from the nasopharynx, although it may rarely arise in extranasopharyngeal sites. Case Report. A 46-year-old male presented with left side nasal obstruction and epistaxis for one month. Clinical nasal examination revealed left sided polypoidal mass arising from the vestibular region of the late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Diseases in the nasopharynx may be of different natures, such as benign or malignant neoplasms, and infectious or inflammatory diseases [ 16 ]. The NA is a neoplasm that accounts for less than 0.5% of all head and neck tumors [ 2 , 5 , 12 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diseases in the nasopharynx may be of different natures, such as benign or malignant neoplasms, and infectious or inflammatory diseases [ 16 ]. The NA is a neoplasm that accounts for less than 0.5% of all head and neck tumors [ 2 , 5 , 12 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…From this suspicion, we decided to perform the incisional biopsy. The different degrees of vascularization of this lesion [ 16 ] may explain the absence of abnormal bleeding during the diagnostic surgical procedure. In addition, it is worth noting that this case does not represent an extranasopharyngeal angiofibroma [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The triad of unilateral nasal occlusion, epistaxis, and a nasopharyngeal neoplasm propose the diagnosis [5]. It has been supposed that NA is a tumor dependent on testosterone [6].…”
Section: Introductionmentioning
confidence: 99%
“…1 Mahmood et al reported the pedicle had been completely transected with bipolar diathermy, with insignificant bleeding which was controlled with electrocautery. 10 The recurrence rate of angiofibroma varies in some series. Sun et al reported the recurrence occurred in 21.7% of the patients with tumor size less than 4 cm and 54.9% of the patients with tumor size more than 4 cm.…”
mentioning
confidence: 99%